Polypropylene-based membrane adsorbers via photo-initiated graft copolymerization: optimizing separation performance by preparation conditions - Mohd. Yusof, Abdul Halim; Ulbricht, Mathias (Elsevier Science B.V., 2007)
Preparation of novel separation membranes can be done very efficiently with controlled surface functionalization. Photo-initiated surface-selective graft copolymerization was performed using a recently developed entrapping method for the photo-initiator benzophenone (BP), and weak cation-exchange polymer brush structures on polypropylene membrane pore surfaces were obtained using acrylic acid (AA) as functional monomer. Copolymerization of AA with "diluent" monomer acrylamide (AAm) and "cross-linker" monomer methylene bisacrylamide (MBAA) were done for variations of the grafted layer. Graft copolymer composition analysis had been performed using FTIR-ATR spectroscopy. Performance characterizations had been done by measurements of membrane permeability at low and high pH as well as at different salt concentrations, by reversible binding of a model protein (lysozyme), by inadvertent pH transient under membrane chromatography conditions and by breakthrough curves for system dispersion analysis. The most important result of this study is that chemical cross-linking within grafted layers with about the same amount of functional groups than those from linear grafted polymer leads to a significant improvement of porous adsorber performance because the dynamic protein binding capacity can be increased, the membrane permeability is significantly increased and it's sensitivity to changes in eluent pH and salt concentration is much decreased, and consequently the solute dispersion within the membrane is reduced as indicated by significantly sharper break-through curves.